2015
DOI: 10.3934/publichealth.2015.1.132
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological, Clinical and Entomological Characteristics of Yellow Fever Outbreak in Darfur 2012

Abstract: The study aims at analyzing the epidemiological, clinical and entomological characteristics of Darfur yellow fever epidemic. It is a descriptive, cross-sectional study. According to operational case definition, suspected yellow fever cases are included in case spread sheet with variables like age, sex, locality, occupation, status of vaccination, onset of symptoms, presenting symptoms, date of blood sampling and confirmation of diagnosis either by laboratory results or epidemiological link. Data about importan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…The majority of cases were seen in 15–44 year-old individuals (75.8% of cases) who may have been infected while working outdoors during the day and dusk, the peak mosquito biting times; a risk factor also described in Kenya (1992–1993) where 81% of cases were <40 years old (Reiter et al, 1998). The overall CFR in SOZ was 37.6%, which is higher than in the Darfur epidemic of 2012 (20.3%) and in Uganda in 2011 (24.9%) (Alhakimi et al, 2015). Only four cases were reported from outside of SOZ (Gamo Gofa, Konso, and Mirab Abaya), which may be from individuals visiting the region, for example, becoming infected at the weekly Saturday market in Jinka Town; rather than autochthonous YFV transmission.…”
Section: Discussionmentioning
confidence: 81%
“…The majority of cases were seen in 15–44 year-old individuals (75.8% of cases) who may have been infected while working outdoors during the day and dusk, the peak mosquito biting times; a risk factor also described in Kenya (1992–1993) where 81% of cases were <40 years old (Reiter et al, 1998). The overall CFR in SOZ was 37.6%, which is higher than in the Darfur epidemic of 2012 (20.3%) and in Uganda in 2011 (24.9%) (Alhakimi et al, 2015). Only four cases were reported from outside of SOZ (Gamo Gofa, Konso, and Mirab Abaya), which may be from individuals visiting the region, for example, becoming infected at the weekly Saturday market in Jinka Town; rather than autochthonous YFV transmission.…”
Section: Discussionmentioning
confidence: 81%
“…The majority of cases were seen in 15-44 year olds (75.8%) who may have been infected while working outdoors during the day and dusk, the peak mosquito biting times; a risk factor also described in Kenya (1992-1993) where 81% of cases were <40 years old (34). The overall CFR in SOZ was 37.6%, which is higher than in the Darfur epidemic of 2012 (20.3%) and in Uganda in 2011 (24.9%) (33). Only 4 cases were reported from outside of SOZ, which may be from individuals visiting the region, e.g.…”
Section: Discussionmentioning
confidence: 81%
“…In SOZ, the CFR in males (48.5%) was almost double compared to females (22.1%), which was consistent with the YF outbreak in Uganda (29.6% in males compared to 17.8% in females) and may be explained by males often reporting later (and sicker) to health facilities, due to underestimating the severity of the disease at symptom onset. By contrast, during outbreaks in The Gambia (1978-1979) and Ghana (1969-1970), children <15 years of age were the most affected, due to the stopping of routine mass YF vaccination campaigns in the early 1960s (33).…”
Section: Discussionmentioning
confidence: 99%
“…Children < 15 years of age accounted for 21.4% of these case-patients, and 15.6% of them had seizures. In the same study, ≈8% of case-patients were reported to have been vaccinated, suggesting that the immunity caused by the vaccine might be affected by other factors that influence the effectiveness and duration of the vaccine ( 8 ).…”
Section: Discussionmentioning
confidence: 97%
“…In a study in Darfur, Sudan, during a 2012 yellow fever epidemic, 844 cases of suspected yellow fever were reported ( 8 ). Children < 15 years of age accounted for 21.4% of these case-patients, and 15.6% of them had seizures.…”
Section: Discussionmentioning
confidence: 99%